2011
DOI: 10.1111/j.1523-1739.2011.01685.x
|View full text |Cite
|
Sign up to set email alerts
|

Relations between Urban Bird and Plant Communities and Human Well-Being and Connection to Nature

Abstract: By 2050, 70% of the world's population will live in urban areas. In many cases urbanization reduces the richness and abundance of native species. Living in highly modified environments with fewer opportunities to interact directly with a diversity of native species may adversely affect residents' personal well-being and emotional connection to nature. We assessed the personal well-being, neighborhood well-being (a measure of a person's satisfaction with their neighborhood), and level of connection to nature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
137
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(143 citation statements)
references
References 33 publications
5
137
1
Order By: Relevance
“…Previous studies support our assumption and the perception of urban green space has often focused on conspicuous plants (Fuller et al 2007;Dallimer et al 2012;Shwartz et al 2014;Carrus et al 2015;Shanahan et al 2015). Moreover, vegetation cover was positively related to personal well-being in a study comprising 9 Australian towns and cities (Luck et al 2011). Future studies on perception of urban vegetation should focus on possible positive covariation between species richness and vegetation cover because it is not well known whether people differentiate between them.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Previous studies support our assumption and the perception of urban green space has often focused on conspicuous plants (Fuller et al 2007;Dallimer et al 2012;Shwartz et al 2014;Carrus et al 2015;Shanahan et al 2015). Moreover, vegetation cover was positively related to personal well-being in a study comprising 9 Australian towns and cities (Luck et al 2011). Future studies on perception of urban vegetation should focus on possible positive covariation between species richness and vegetation cover because it is not well known whether people differentiate between them.…”
Section: Discussionsupporting
confidence: 52%
“…Previous investigations in urban green space in England have indicated that bird species richness can be positively associated with Bcontinuity with past and attachment ( Fuller et al 2007). Luck et al (2011) found bird abundance to be related to personal well-being but only weakly. In our sampling we also included bumblebees because they are highly conspicuous arthropods and their abundance in cities is often positively associated with an abundance of flowering plants (Matteson and Langellotto 2010;Gunnarsson and Federsel 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that homes surrounded by more greenery (e.g., trees and grass) are associated with reduced internal family conflict (71). A more recent study demonstrated a positive effect of vegetation on the personal well-being of city dwellers and weak positive associations of wellbeing with species richness and bird abundance (72). Deep interconnections have been found between mental well-being and living in close relationship with animals.…”
Section: Livingmentioning
confidence: 99%
“…Carbon storage helps mitigate climate change at the global scale by offsetting the urban footprint [37], while at the regional and local scale it contributes to improving air quality [12,26]. Habitat provision in the urban landscape is strongly linked to biodiversity and to the well-being of urban inhabitants [23,[38][39][40][41][42][43]. In comparison to carbon and biodiversity, recreation potential has a more local effect as it relates to the provision of space for leisure, contemplation and exercising which has been linked to improve public health [44].…”
Section: Introductionmentioning
confidence: 99%